KADAR PROTEIN, KADAR LEMAK, KADAR AIR, DAN TOTAL MIKROBA BAKSO DAGING SAPI YANG DIOLAH DENGAN PENGENYAL TEPUNG KELADI, TEPUNG TAPIOKA DAN ASAP CAIR TEMPURUNG KELAPA - Sukisman Abdul Halid; Abdul Rahim; Minarny Gobel; If'all If'all (Universitas Wahid Hasyim, 2023)
The lifestyle and eating patterns of the community make residents more demanding for instant food products and guaranteed food safety for consumption. One of the foodstuffs that are in great demand by the public is beef meatballs. The process of making meatballs generally uses ingredients a tapioca starch thickener that can create meatballs with the characteristics of taste, chewy, compact, and juicy that are favored by consumer .In addition to the use of tapioca flour as a meatball thickener, it is necessary to look for other thickening agents as a meatball thickener, namely taro flour as a safe alternative to use as a natural thickener in the manufacture of meatballs. In this research, an analysis of the physical and chemical properties was attempted, including protein content, fat content, water content, as well as an analysis of the total microbial( Total Palte Count/ TPC) beef meatballs processed with taro flour, tapioca flour, and coconut shell liquid smoke. The results showed that the highest protein content was obtained in the B2 meatball sample, namely 12, 22+ 0. 12% and the lowest was obtained in the B3 meatball sample, which was 9. 11+ 0. 54%, the highest fat content was obtained in the B2 sample code, namely 0, 24+ 0, 01% and the lowest was obtained in sample code B4 of 0, 17+ 0, 01%, the highest water content obtained in sample code B1 of 76, 10+ 0. 67%, and the lowest was obtained in sample code B0( control) of 70, 20+ 0. 03%, and the highest average total number of microbes was obtained in sample code B4 which was 5, 92+ 0. 12 log cfu/ gr, and the lowest was obtained at sample code B1 of 0. 07+ 0. 07 log cfu/ gr.